The Earnings Differential between Formal and Informal Employees in Urban China - Hong Zuo (Contemporary Economics, 2013)
Few studies in the field of labor economics have analyzed the earnings differential between formal and informal employees in urban China. Due to data limitations, previous studies on this subject have not yielded accurate and widely acceptable results. This study seeks to obtain more accurate results by analyzing the earnings differential based on the conceptual framework of informal employment developed by the 17th International Conference of Labor Statisticians. We analyzed data from the 2006 Chinese General Social Survey, using the Lee model to correct for selection bias and decomposing the earnings differential between formal and informal employees in urban China in terms of the effects of employee characteristics, employment, and working hours. The latter two of these comprise the segmentation effect. We found that only 33% of the observed earnings differential can be explained by employee characteristics; the remaining 67% is attributable to the segmentation effect. The working hours effect narrows the earnings differential. Based on the results of our analysis, we conclude that informal employees in urban China, especially female informal employees, suffer from segmentation and that policies to address segmentation issues are needed.